The United Kingdom - Walsh, Kieran (Vero Beach, Florida Rourke Publishing, 2005)
This series introduces young readers to places that are not like the United States. The book presents information about the land, people, sports, school, food and holidays. Special features include a map, the country's flag and a Fast Fact page.
1 - 6
Keywords: United Kingdom; Great Britain; Northern Ireland